IDENTIFIKASI BAHAYA KIMIA, PENILAIAN RISIKO, DAN PENGENDALIAN RISIKO PENGGUNAAN BAHAN KIMIA PADA PEKERJA AREA MIXING PT X TAHUN 2023 - Reini Syahbani Fatah (2024)
PT X is a solid soap manufacturing industry that utilizes chemical raw materials. Direct contact with these chemicals during work activities has led to skin and eye irritation among some workers. The aim of this research was to identify hazards, assess risks, and provide recommendations for controlling the risks associated with chemical substance usage, using the HIRARC method. This research used a qualitative approach involving in-depth interviews, observations, and document reviews. The informants consisted of five individuals, including 1 Head of HSE, 1 supervisor, and 3 workers, selected through purposive sampling technique. The hazard identification was based on potential risks to human, material, machinery/equipment, methods, and the environment. The residual risk assessment results revealed 21 potential hazards, comprising 5 categorized as medium and 16 as low. It was necessary to replace cresylic acid with natural substances such as tea tree oil, install dust collectors throughout the area with stronger suction power, conduct inspections of personal protective equipment during briefings, and provide long-sleeved hygiene garments and chemical-resistant gloves.